Firehouse! - Teague, Mark. (New York : Orchard Books, 2010)
Edward and his cousin Judy come for a visit to the firehouse and learn how everything works with some unexpected results.
Kirkus Review, April 2010.
Kirkus Review.
2.8
K-3
Keywords: Fire departments -- Juvenile fiction; Fire extinction -- Juvenile fiction; Fire departments -- Fiction; Fire extinction -- Fiction; Fire departments -- Fiction; Fire prevention -- Fiction; Fire fighters -- Fiction; Fire departments -- Fiction; Dogs -- Fiction; Picture books for children